Meningkatkan Kompetensi Guru Melalui Pelatihan Penulisan Karya Tulis Ilmiah Dan Publikasi Jurnal Ilmiah Berbasis Open Journal System (OJS) Di MTs Negeri 32 Jakarta - Adi Nur Rohman; Sugeng Sugeng (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Among the models of continuous professional development for teachers are potential development and increasing scientific cultural traditions through scientific publications. The obligation of scientific publications for teachers is strengthened by the Minister of Administrative and Bureaucratic Reform Regulation Number 16 of 2009 concerning Teacher Functional Positions and Credit Scores. However, in reality, scientific publications from teachers are still very minimal. The partner of this PKM activity is MTsN 32 Jakarta where the problem faced is the lack of teacher knowledge in terms of technical writing of scientific papers. In addition, it is a new thing for MTsN 32 Jakarta teachers to publish in OJS-based scientific journals. This PKM activity provides solutions for partners in the form of training in writing scientific papers and publications in OJS-based scientific journals as an effort to improve teacher competence so that it has an impact in realizing professional and competent educators.